Cellular pathways involved in the ex vivo expression of bovine leukemia virus. - Kerkhofs, P (1996)
Bovine leukemia virus (BLV) is the etiologic agent of enzootic bovine leukosis. The virus adopts a strategy based on the lack of viral expression in vivo; only very rare BLV-infected B lymphocytes express viral information. When the cells are isolated from animals in persistent lymphocytosis and cultivated ex vivo, a tremendous increase in viral expression occurs. To gain insight into this mechanism, we employed a general approach using chemicals that interfere specifically with cellular pathways involved in signal transduction from the cell membrane to the nucleus. Our data demonstrate that BLV expression is not correlated with the activity of protein kinase A (PKA) and is even inhibited by cyclic AMP (cAMP). The cAMP/PKA pathway is thus apparently not involved in ex vivo viral expression. In contrast, PKC appears to play a key role in this process. Phorbol myristate acetate can directly activate viral expression in B cells (in the absence of T cells). Furthermore, calphostin C, a highly specific inhibitor of PKC, partly decreases ex vivo BLV expression. Our data further demonstrate that calmodulin and calcineurin, a calmodulin-dependent phosphatase, play a key role in the induction of viral expression. The involvement of this calmodulin-dependent pathway could explain the induction of expression that cannot be assigned to PKC. Furthermore, it appears that the activation of viral expression requires a calmodulin but not a PKA-dependent pathway. These data highlight major differences between transient transfection and ex vivo experiments. Finally, despite their homologies, BLV and human T-cell leukemia virus appear to use different signal transduction pathways to induce viral expression.